Understanding and influencing public support for insurgency and terrorism - Davis, Paul K., 1943-; Larson, Eric V. (Eric Victor), 1957-; Haldeman, Zachary; Oguz, Mustafa; Rana, Yashodhara; National Defense Research Institute (U.S.). International Security and Defense Policy Center; Rand Corporation; United States. Department of Defense. Office of the Secretary of Defense (Santa Monica, CA : RAND, 2012)
Building on earlier RAND research that reviewed and integrated social science relevant to understanding terrorism and counterterrorism, this volume focuses on public support for both insurgency and terrorism and incorporates insights stimulated by social movement theory. The authors examine four case studies: al-Qa$1 (Bida$1 (Bs transnational jihadist movement, the Taliban insurgency in Afghanistan, the Kurdistan Workers Party (PKK) in Turkey, and the Maoist insurgency in Nepal. The authors first developed a model, based on previous work, identifying the factors that influence public support for insurgency and terrorism and how these factors relate to each other. They then drew on extensive primary- and secondary-source material from each of the four case studies to evaluate and refine the model. Comparing the four case studies, the authors discuss which factors were most salient across cases and how their importance varied in each case. Finally, they offer a model of (3z(Bpersuasive communications(3y (Bthat connects the study$1 (Bs research to issues of strategy and policy.s
Introduction -- A Conceptual Model -- The Case of al-Qa$1 (Bida -- Public Support for the Taliban Insurgency in Afghanistan -- Public Support for the Kurdistan Workers Party (PKK) in Turkey -- Public Support for the Maoists in Nepal -- Comparisons and Implications for Analysis of Strategy -- Appendix: Polling on Public Support for Terrorism in the Islamic World.s
"RAND National Defense Research Institute."
"This research was ... conducted within the International Security and Defense Policy ISDP) Center of the RAND National Defense Research Institute"--Preface.
Includes bibliographical references (p. 203-232).
Also available on the internet via WWW in PDF format.
Keywords: Partiya Karkeren Kurdistane -- Public opinion; Qaida (Organization) -- Public opinion; Taliban -- Public opinion; Insurgency -- Public opinion -- Case studies; Terrorism -- Public opinion -- Case studies; Nepal -- History -- Civil War, 1996-2006 -- Public opinion